Studium senzitivity signální dráhy přes receptor Notch na aminokyseliny v potravě - Steffal, Pavel (Jihočeská univerzita, 2018)
The sensitivity of Notch signaling pathway to metabolism has been proposed in several recent studies but it is unclear if the changes in fly diet composition can directly lead to changes in Notch phenotype in vivo. In this work we show that activity of Notch pathway is sensitive to amino acids via the TOR pathway. In addition we will test a candidate protein as a sensor for amino acid level in the fat body of Drosophila melanogaster but also independently in other tissues.
Study of signaling pathway sensitivity via the Notch receptor to amino acids in the diet
Keywords: Notch; aminoacids; metabolism; TOR; Notch; aminoacids; metabolism; TOR